Pemanfaatan Sumber Informasi Nelayan dalam Adaptasi Ekonomi di Desa Bokori Kecamatan Soropia Kabupaten Konawe - Mahmud, Mahmud; Buana, Tjandra; Wunawarsih, Ima Astuty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The purpose of this study was to find out the sources of fisheries in economic adaptation in the village of Bokori, Soropia District, Konawe District. This research was conducted in Bokori Village, Soropia District, Konawe Regency. The type of research used for people is 33 people. Data analysis uses a quantitative approach. The results of this study indicate that the use of Fisherman Information Sources in Economic Adaptation in Bokori Village, Soropia District, Konawe Regency is in the moderate category. Sources of information in this study include the village head, village secretary, fish collectors, marine retainer, papalele, and fisherman associates